First Example of a Modular Porphyrinoid Assembly Capable of Stabilizing Different Metal Ions in a Single Molecular Scaffold. Issue 41 (4th August 2015) - Murugavel, Muthuchamy; Reddy, R. V. Ramana; Dey, Dhananjay; Sankar, Jeyaraman
Abstract We report the synthesis and characterization of porphyrin–corrole–porphyrin (Por‐Cor‐Por) hybrids directly linked at the meso–meso positions for the first time. The stability and solubility of the trimer are carefully balanced by adding electron‐withdrawing substituents to the corrole ring and sterically bulky groups on the porphyrins. The new hybrids are capable of stabilizing more than one metal ion in a single molecular scaffold. The versatility of the triad has been demonstrated by successfully stabilizing homo‐ (Ni) and heterotrinuclear (Ni‐Cu‐Ni) coordination motifs. The solid‐state structure of the NiPor‐CuCor‐PorNi hybrid was revealed by single‐crystal X‐ray diffraction studies. The NiII porphyrins are significantly ruffled and tilted by 83° from the plane of corrole. The robustness of the synthesized hybrids was reflected in the electrochemical investigations and the redox behaviour of the hybrids show that the oxidation processes are mostly corrole‐centred. In particular it is worth noting that the Por‐Cor‐Por hybrid can further be manipulated due to the presence of substituent‐free meso‐positions on both the terminals.